Design of R.C.C. Framed Structure Considering the Effect of Stiffness of Slab A Review - Bhojram; Nirmal, Pradeep Kumar; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2022)
The slab is a crucial structural component and one of the members that uses the most concrete. The slab thickness increases as the load on it increases or as the space between columns becomes more clear. Due to the increased consumption of materials like steel and concrete, the slab’s self-weight increases. Therefore, by taking the slab’s stiffness into account, the self-weight of the slab can be reduced. The ability of a structure to withstand deformation is indicated by its stiffness. The purpose of this study is to comprehend how moments created in columns behave when the slab’s stiffness is taken into account. The behaviour of floor slabs in the frame as a result of vertical loading and the moments created in columns was the major focus of the current paper. The frame has been modelled using STAAD software both with and without taking slab stiffness into account.